Siglec-15 on osteoclasts is crucial for bone erosion in serum-Transfer arthritis - Korn, Marina; Schmitt, Heike; Angermüller, Sieglinde; Chambers, David; Seeling, Michaela; Lux, Uwe; Brey, Stefanie; Royzman, Dmytro; Bruckner, Christin; Popp, Vanessa; Percivalle, Elena; Bäuerle, Tobias; et al. (Journal of Immunology, 2020)
Siglec-15 is a conserved sialic acid binding Ig-like lectin, which is expressed on osteoclasts. Deficiency of Siglec-15 leads to an impaired osteoclast development, resulting in a mild osteopetrotic phenotype. The role of Siglec-15 in arthritis is still largely unclear. To address this, we generated Siglec-15 knockout mice and analyzed them in a mouse arthritis model.We could show that Siglec-15 is directly involved in pathologic bone erosion in the K/BxN serum-Transfer arthritis model. Histological analyses of joint destruction provided evidence for a significant reduction in bone erosion area and osteoclast numbers in Siglec-152/2 mice, whereas the inflammation area and cartilage destruction was comparable to wild-Type mice. Thus, Siglec-15 on osteoclasts has a crucial function for bone erosion during arthritis. In addition, we generated a new monoclonal anti Siglec-15 Ab to clarify its expression pattern on immune cells. Whereas this Ab demonstrated an almost exclusive Siglec-15 expression on murine osteoclasts and hardly any other expression on various other immune cell types, human Siglec-15 was more broadly expressed on human myeloid cells, including human osteoclasts. Taken together, our findings show a role of Siglec-15 as a regulator of pathologic bone resorption in arthritis and highlight its potential as a target for future therapies, as Siglec-15 blocking Abs are available.
CRIS-Team Scopus Importer:2020-11-20